Gender‐related sensitivity of development and growth to real microgravity in Xenopus laevis. Issue 1 (30th September 2013) - Horn, Eberhard R.; Gabriel, Martin
ABSTRACT Exposure of organisms to microgravity can induce morphological, physiological, and behavioral modifications which normalize after re‐entry in 1g‐condition within hours to few weeks. Development of Xenopus laevis tadpoles, their metamorphosis, and adults' growth were monitored for 3 years after their flight on the 12‐day Soyuz mission TMA13 to the International Space Station. At onset of microgravity, tadpoles had just developed the hind limb (stage 47) or forelimb bud (stage 50). Recordings during the first 4 days after landing revealed no differences of developmental progresses and growth between flight and ground tadpoles. Further development and growth were strongly retarded in all animals; nevertheless, significant differences appeared between flight and ground groups during this postflight period. They include (1) acceleration of development in stage 47 but not stage 50 flight tadpoles; (2) earlier metamorphosis of stage 47 flight tadpoles compared to their 1g‐ground controls while stage 50 flight tadpoles metamorphosed later than their ground controls; (3) maintenance of a tail during the juvenile stage exclusively in some stage 47 flight animals, and (4) accelerated growth of stage 47 male flight toads but retarded growth of stage 50 flight males compared to the respective 1g‐ground control males. No difference of growth was detected between flight and ground females after metamorphosis. All differences between flight and ground animals disappeared 1 year after landing. We conclude (1) that limited spatial and nutritional conditions during the mission period caused developmental retardation, and (2) that the thyroid gland of Xenopus is susceptible to spatial environment, in particular, during the period of beginning activation. J. Exp. Zool. 321A: 1–12, 2014. © 2013 Wiley Periodicals, Inc.